On Some Results for M-band Sub Filter Bank - MohammedaliHasan, Hisham; Galib Atshan, Waggas; Sahib Kadhim, Ghufran (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In the present paper, we study aliasing signal, filter banks-band and sub M-band. Weobtain some results, like, the relationship between input and output signal, subsampling, input signal, output signal.